ANALISIS KESULITAN BELAJAR SISWA SMP PADA MATERI BANGUN DATAR - Zaeri, Annisah; Leja, Ertha Agnia Maulina; Fajriah, Khadijatul; Angraini, Lilis Marina (Journal of Research in Science and Mathematics Education, 2024)
Purpose: This research aims to analyze the difficulties experienced by junior high school students with two-dimensional space concepts. Methodology: This quantitative research employs a descriptive approach. The subjects were 30 seventh-grade students at Pekanbaru Da'wah Middle School, Indonesia. The research object is the students' test results regarding the concept of two-dimensional space. Data collection involved asking students to complete essay test questions. Findings: The results show that 50% of students had difficulty with the indicator "Applying concepts to solve problems." For the indicator "Using appropriate formulas and completing calculations correctly and accurately," 43.3% of students (13 out of 30) struggled. Regarding the indicator "Relating problems to everyday life," 30% of students (9 out of 30) experienced difficulties. Significance: The next stage is grouping students' abilities according to the indicators. It can be concluded that seventh-grade students at SMPN 1 still experience difficulties with questions on two-dimensional space.